Edukasi dan Pembekalan Kewirausahaan Desa Bojongcae, Kecamatan Cibadak, Lebak Banten - Sugianto Sugianto; Ullya Vidriza; Nani Ariani (Universitas Persada Indonesia YAI, 2023)
The essence of national development is full human development and the development ofIndonesian society as a whole, this can be realized if the welfare of the family and society can beachieved properly. In the context of realizing family and community welfare, among others,community empowerment can be done and in fact community empowerment has not been maximized,so that family and community welfare has not been fully achieved, because family and communitybusinesses have not been able to develop their potential and roles optimally. The condition of smallbusinesses is still relatively weak, some are still limited to efforts to meet local consumption needsor the environment in which the business is located, so it is necessary to strengthen the organizationand increase the participation of community members in activities that are productive in the formof entrepreneurship, among others; training activities for making painting shoes and other realsectors. These weaknesses must be overcome and the role of universities as educational institutionscan be more involved and help overcome existing problems so that it is hoped that communitymembers or organizations can continue to play a role in Indonesia's economic growth anddevelopment. Recognizing these problems, we are Lecturers of the Faculty of Economics andBusiness, UPN Veterans Jakarta, one of the universities that cares about the surrounding communityand plans to carry out community service activities which are expected to increase knowledge inentrepreneurship education and training, with the aim of providing an understanding of the conceptof entrepreneurship. and understand the methods or methods of entrepreneurship, which will beuseful in increasing family income and the regional economy. The results of the implementation ofcommunity service show that generally the PKK group of Bojongcae Village, Cibadak District Lebak Regency, Banten understands, this is in accordance with the planned targets of targets above80%.